Perturbation Analysis of Rivlin-Ericksen Fluid on Heat Transfer in the Presence of Heat Absorption - Sudarshan Reddy, Y.; Balamurugan, K. S.; Dharmaiah, G. (Asian Journal of Engineering and Applied Technology, 2019)
The problem of visco-elastic Rivlin-Ericksen fluid flow past a semi- infinite vertical plate embedded in a porous medium with variable temperature and suction in the presence of a uniform transverse magnetic field and thermal buoyancy effect is considered. The plate is assumed to move with a constant velocity in the direction of fluid flow while the free stream velocity is assumed to follow the exponentially increasing small perturbation law. Time-dependent wall suction is assumed to occur at the permeable surface. The dimensionless governing equations for this investigation are solved analytically using two-term harmonic and non-harmonic functions. Numerical evaluation of the analytical results is performed and some graphical results such as visco-elastic parameter Rm, heat absorption parameter Q, Grashof number Gr, Prandtl number Pr, time t, suction velocity parameter A, moving velocity parameter Up and an exponential parameter ε, for the velocity and temperature profiles within the boundary layer are presented. Skin-friction coefficient, Nusselt numbers are also discussed with the help of the tables.